The Impact of COVID-19 on Global Stock Markets: Comparative Insights from Developed, Developing, and Regionally Integrated Markets - Babatounde Ifred Paterne Zonon; Mouhamed Bayane Bouraima; Chuang Chen; Koffi Dumor (Economies)
This study examines the impact of the COVID-19 pandemic on global stock markets by comparing developed and developing economies, while highlighting regional differences. Using dynamic panel regression models, this study explores the role of pandemic-related variables, fiscal policies, and investor sentiment in shaping market performance. Developed markets, although highly sensitive to infections, benefited from robust fiscal interventions and institutional resilience. Developing markets face greater volatility owing to stringent measures, structural vulnerabilities, and limited fiscal capacities. Regionally, Europe demonstrated resilience through coordinated policies, whereas the Americas experienced significant volatility from fragmented responses. Africa and parts of Asia encountered fewer initial shocks but struggled with prolonged recovery due to limited financial and institutional resources. The findings underscore the importance of economic integration, coordinated fiscal and monetary policies, and investor sentiment management to stabilize markets during crises. These insights guide policymakers in enhancing resilience and fostering sustainable economic growth amid future global disruptions.